A Journey through the Generations to Clear a Painful Legacy through Psychodrama - Galabina Tarashoeva; Cristina Schmidt; Petra Marinova-Djambazova (Revista Brasileira de Psicodrama)
The application of psychodrama in transgenerational trauma therapy has some peculiarities. In this paper, a complete psychodrama session is presented with a case containing examples of Invisible family loyalties, Unfinished grieving, Accountability across generations, and the Replacement child. The protagonist in the presented case is a 37-year-old woman who lost her brother when he was 21 years old; her family history is full of men who died very young, and she experiences constant unreasonable feelings of loss, as well as fear of losing her sons, although she does not believe in curses.